2008
DOI: 10.1097/brs.0b013e318183bb86
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Tumor Necrosis Factor-Alpha in Periradicular Fat Tissue in Patients With Radiculopathy From Herniated Disc

Abstract: Higher concentrations of TNF-alpha were found in EF from patients with radiculopathy from HD compared with patients suffering from other type of back pain. These results support the role of TNF-alpha in the pathogenesis of radiculopathy from HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 29 publications
2
44
0
5
Order By: Relevance
“…In recent clinical studies, elevated levels of proinflammatory cytokines (IFN-c, IL-1b, IL-2, IL-6 and TNF-a) correlated with elevated pain scores in various types of neurological and rheumatologic disorders [11][12][13][14][15][16][17][18][19][20]. In addition, we found that intervertebral TNF-a levels correlate with preoperative pain in LDH patients [21].…”
Section: Discussionsupporting
confidence: 52%
“…In recent clinical studies, elevated levels of proinflammatory cytokines (IFN-c, IL-1b, IL-2, IL-6 and TNF-a) correlated with elevated pain scores in various types of neurological and rheumatologic disorders [11][12][13][14][15][16][17][18][19][20]. In addition, we found that intervertebral TNF-a levels correlate with preoperative pain in LDH patients [21].…”
Section: Discussionsupporting
confidence: 52%
“…The sciatica syndrome is characterized by low back pain with radiculopathy [12]. Sciatica often has a lengthy course and causes prolonged disability [21,41].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation of the spinal nerve root induced by autologous NP has been documented by many experimental animal studies [21] . Results of the current study support the concept that nerve inflammatory responses may be associated with NP leakage.…”
Section: Discussionmentioning
confidence: 99%